2008
DOI: 10.1177/096739110801600705
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Cost-Effective Polypropylene Composites Filled with Red-Mud Particles

Abstract: In recent years, the use of filler materials, such as red mud, in composites has increased. In this study, the use of industrial waste red mud as a filler material in an isotactic polypropylene (iPP) polymer–matrix composite (PMC) was investigated. A variety of mechanical tests were performed on the unreinforced polymer and on composites with 10, 20, 30, 40 and 50 wt.% red mud. Tensile strength, three-point flexural strength and hardness tests have been carried out, and the relationships between the red-mud co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…Of organic fillers, carbon black (CB) have gained much attention in fabrication of polymeric composites, because CB reinforced composites are being exploited in many industrial and domestic appliances including self-regulating heating elements, current switching, fluid sensor, thermal controller, capacitors and electromagnetic interference shielding . However, research works found on filler reinforced polymer composites are mostly based on isotactic polypropylene (Akinci 2009, Mina et al 2010, though a few research works on filler loaded PE composites have been published (Ulutan et al 2000, Yuan et al 2003, Dang et al 2003, Luyt et al 2006. In addition, homogeneous dispersion of fillers in polymer matrix by melt blending has also been a challenging task.…”
Section: Introductionmentioning
confidence: 99%
“…Of organic fillers, carbon black (CB) have gained much attention in fabrication of polymeric composites, because CB reinforced composites are being exploited in many industrial and domestic appliances including self-regulating heating elements, current switching, fluid sensor, thermal controller, capacitors and electromagnetic interference shielding . However, research works found on filler reinforced polymer composites are mostly based on isotactic polypropylene (Akinci 2009, Mina et al 2010, though a few research works on filler loaded PE composites have been published (Ulutan et al 2000, Yuan et al 2003, Dang et al 2003, Luyt et al 2006. In addition, homogeneous dispersion of fillers in polymer matrix by melt blending has also been a challenging task.…”
Section: Introductionmentioning
confidence: 99%
“…This causes a considerable plastic deformation of material. In can be asserted that the system of such composites has a low cohesive strength, which is corroborated by investigations [14][15][16][17][18]. The return of specimen to its original shape after unloading is evidence of elastic properties of material and hence of its high cohesion characteristics.…”
mentioning
confidence: 55%
“…The value of ΔH 0 PP (Tm) has previously been reported to be 207 J/g for PP [40]. From Table 4, the weight fraction crystallinity was calculated to approximately 40 wt % for WEEEBR and TBV, while it was slightly lower for TBR.…”
Section: Thermal Propertiesmentioning
confidence: 83%